Concepções geométricas de percepção e representação da forma no desenho - Ribeiro, Ailton César; Nascimento, Roberto Alcarria do; Benutti, Maria Antonia [UNESP] (My University, 2014)
A study on means of developing of perception and reading of the form by the conception and development of a Teaching Methodology of Drawing with emphasis in its early stages, its development and application in the initial stages of the Design process, dissecting it as a mental and physical process. We will be addressing the contributions of Geometry as a mean of simplification of the reading and materializing configurations as some pointers for addressing the Drawing teaching in the reported course.

Um estudo sobre meios de desenvolvimento da percepção e leitura da forma pela concepção e desenvolvimento de uma metodologia de ensino do Desenho com ênfase nas suas fases iniciais, seu desenvolvimento e aplicação nas primeiras etapas do processo de projeto em Design, dissecando-o como processo mental e físico. Abordaremos a contribuição da geometrização como meio de simplificação das dinâmicas de leitura e materialização de configurações como alguns indicadores para se pensar o ensino do Desenho no referido curso.
Geometric concepts of perception and representation of the shape of the drawing
Keywords: Drawing; Teaching; Drawing teaching; Geometry; Perception; Design; Desenho; Ensino; Ensino do desenho; Geometria; Percepção; Design